2008
DOI: 10.3174/ajnr.a0975
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Alberta Stroke Program Early CT Score during the First 3 Hours of Middle Cerebral Artery Stroke: Comparison of Noncontrast CT, CT Angiography Source Images, and CT Perfusion

Abstract: BACKGROUND AND PURPOSE:The Alberta Stroke Program Early CT Score (ASPECTS) is a reliable method of delineating the extent of middle cerebral artery (MCA) stroke. Our aim was to retrospectively compare the accuracy of ASPECTS on noncontrast CT, CT angiography (CTA) source images, and CT perfusion maps of cerebral blood volume (CBV) during the first 3 hours of middle cerebral artery (MCA) stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 20 publications
2
58
0
6
Order By: Relevance
“…In ASPECTS topography, the MCA territory was divided into 10 regions (caudate, lentiform nucleus, internal capsule, insula, and M1-M6). [13][14][15] The ASPECTSs of arterial phase and venous phase CTP-SIs were reviewed first, and CBF and CBV were interpreted at least 1 week later to limit potential recall bias. The raters assessed the imaging independently, blinded to clinical information, and did not know follow-up imaging results.…”
Section: Imaging Analysismentioning
confidence: 99%
“…In ASPECTS topography, the MCA territory was divided into 10 regions (caudate, lentiform nucleus, internal capsule, insula, and M1-M6). [13][14][15] The ASPECTSs of arterial phase and venous phase CTP-SIs were reviewed first, and CBF and CBV were interpreted at least 1 week later to limit potential recall bias. The raters assessed the imaging independently, blinded to clinical information, and did not know follow-up imaging results.…”
Section: Imaging Analysismentioning
confidence: 99%
“…Both CT angiography and MR angiography can be used to characterize intravascular thrombi. CT perfusion is a functional imaging technique that can be used to identify salvageable brain tissue [1,2]. Diffusion-weighted MR imaging can be used for identifying infarcted brain tissue that is irreversibly damaged, whereas perfusion-weighted MR imaging can be used for identifying reversibly injured ischemic brain tissue [3].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate inspection of CTA-SI with narrow windows enables definition of the ischemic core with the additional advantage of whole brain coverage. identifying infarct "core" compared with unenhanced CT has been unequivocally established in multiple studies 2,3 . Theoretical modeling indicates that CTA-SI obtained using early generation protocols generates predominantly blood volume-weighted rather than blood flowweighted images.…”
mentioning
confidence: 99%
“…Thus, radiologists should interpret CTP maps in conjunction with CTA-SI data. Finally, it is again worth underscoring that with the newer, more flow-weighted CTA protocols, not every acute CTA-SI hypodense ischemic lesion is destined to infarct; a substantial portion of a CTA-SI hypodense lesion may reflect "at-risk" ischemic penumbra, or even benign oligemia 3 . Moreover, Kamalian et al 4 reported that CBF maps optimally correlate with admission diffusion-weighted imaging.…”
mentioning
confidence: 99%